2005
DOI: 10.1007/s00435-005-0111-5
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of female genital tracts in Dasypodidae (Xenarthra, Mammalia): a comparative survey

Abstract: Previous works about comparative spermatology in Dasypodidae determined that sperm morphology is a striking variable among genera. It was suggested that this sperm feature may be related to specific morphologies of the female reproductive tract. The present comparative study of the morphology of the female genital tract from seven species corresponding to six genera of Dasypodidae is aimed to determine the main similarities and differences between the species and to establish a possible correlation with the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
2
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 11 publications
1
28
2
5
Order By: Relevance
“…Regarding vaginal cytology, it was not conducted everyday because the six‐banded armadillos' females present a small vulvar commissure that makes the introduction of the swab difficult, demanding the use of an anaesthetic protocol for this procedure. This characteristic is similar to that verified for other armadillo species, as C. villosus, C. vellerosus, Zaedyus pichiy, Chlamyphorus chacoensis, Chlamyphorus truncatus and Dasypus hybridus , in which the authors report difficulty in monitoring the oestrous cycle through vaginal cytology (Cetica et al., ; Luaces et al., ). Because of this, accurate identification of the different oestrous cycle phases (proestrus, oestrus, metestrus, dioestrus) was not possible in six‐banded armadillos, but we only distinguished the oestrogen phase from the progesterone phase at using the association of parameters studied.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Regarding vaginal cytology, it was not conducted everyday because the six‐banded armadillos' females present a small vulvar commissure that makes the introduction of the swab difficult, demanding the use of an anaesthetic protocol for this procedure. This characteristic is similar to that verified for other armadillo species, as C. villosus, C. vellerosus, Zaedyus pichiy, Chlamyphorus chacoensis, Chlamyphorus truncatus and Dasypus hybridus , in which the authors report difficulty in monitoring the oestrous cycle through vaginal cytology (Cetica et al., ; Luaces et al., ). Because of this, accurate identification of the different oestrous cycle phases (proestrus, oestrus, metestrus, dioestrus) was not possible in six‐banded armadillos, but we only distinguished the oestrogen phase from the progesterone phase at using the association of parameters studied.…”
Section: Discussionsupporting
confidence: 84%
“…Regarding the ovary dimensions identified by ultrasonography in six‐banded armadillos, they are similar to that previously measured during necropsies in the same species (0.8 × 0.44 mm; Rezende et al., ), and also similar to that reported for other armadillos as the T. matacus (0.8–1.0 cm) and C. villosus (0.6–1.0 cm). However, the armadillos C. vellerosus (0.5 cm), Z. pichiy (0.4 cm) and C. truncates (0.2–0.3 cm; Cetica et al., ) present lower ovary dimensions than that verified in this study. Such information evidenced the variation on reproductive aspects among different armadillo species and emphasized the efficiency of ultrasonography for ovary investigation.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Animals immobilised in this way must be closely monitored for signs of hypothermia. Cetica et al (2005) described the morphology of the female reproductive tract and found it to have ovoid, elongate ovaries with longitudinally polarised cortex and medulla, and several oocytes in each follicle. The uterus was simple and pear-shaped, and the uterine cervix is long as in all armadillos.…”
Section: Smith P 2007 -Southern Three-banded Armadillo Tolypeutes Matmentioning
confidence: 99%
“…La mayoría de los datos existentes hacen referencia a su distribución geográfica y tipo de hábitat; sin embargo, también se han realizado estudios citogenéti-cos (Luaces et al, 2010), placentarios (Adamoli et al, 2001) y sobre la morfología del aparato reproductor de las hembras (Cetica et al, 2005). Además, existen datos etológicos y alimenticios de un individuo mantenido en cautiverio hasta su muerte súbita (Nellar et al, 2008).…”
unclassified